2018
DOI: 10.1242/dev.155283
|View full text |Cite
|
Sign up to set email alerts
|

RBX2 maintains final retinal cell position in a DAB1-dependent and -independent fashion

Abstract: The laminated structure of the retina is fundamental for the organization of the synaptic circuitry that translates light input into patterns of action potentials. However, the molecular mechanisms underlying cell migration and layering of the retina are poorly understood. Here, we show that RBX2, a core component of the E3 ubiquitin ligase CRL5, is essential for retinal layering and function. RBX2 regulates the final cell position of rod bipolar cells, cone photoreceptors and Muller glia. Our data indicate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 78 publications
2
20
0
Order By: Relevance
“…As expected, efficient and extensive depletion of Rbx2 was observed in Rbx2cKO-Emx1 samples at P1 when tested by western blotting (Figure 4C and Figure S1A). Furthermore, Rbx2cKO-Emx1 telencephalons accumulated tyrosine phosphorylated (pY)-Dab1, Dab1, and Fyn, and showed the same layering defects as previously described for Rbx2cKO-Nes pups (Figure S1) (Fairchild et al, 2018; Simo and Cooper, 2013). These results indicate that Rbx2cKO-Emx1 mice faithfully recapitulate the phenotypes observed in Rbx2cKO-Nes mice without the morbidity caused by hydrocephalus.…”
Section: Resultssupporting
confidence: 77%
See 3 more Smart Citations
“…As expected, efficient and extensive depletion of Rbx2 was observed in Rbx2cKO-Emx1 samples at P1 when tested by western blotting (Figure 4C and Figure S1A). Furthermore, Rbx2cKO-Emx1 telencephalons accumulated tyrosine phosphorylated (pY)-Dab1, Dab1, and Fyn, and showed the same layering defects as previously described for Rbx2cKO-Nes pups (Figure S1) (Fairchild et al, 2018; Simo and Cooper, 2013). These results indicate that Rbx2cKO-Emx1 mice faithfully recapitulate the phenotypes observed in Rbx2cKO-Nes mice without the morbidity caused by hydrocephalus.…”
Section: Resultssupporting
confidence: 77%
“…Our previous studies indicate that Rbx2 regulates neuron positions in the retina through cell autonomous and non-autonomous mechanisms (Fairchild et al, 2018). To test whether CRL5 regulates hippocampal development cell autonomously, we used in utero electroporation (IUE) to deplete CRL5 activity in individual PNs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The high level of genetic conservation of glia in the animal kingdom suggests there may be basic principles of glial biology (Charlton‐Perkins et al, ), and the finding here that several conserved genes are involved during particular temporal windows of MG morphogenesis, suggest that there may also be conserved programs of differentiation. A recent study has implicated some proteins found here in mouse MG morphology and tiling including Rbx2, Dab1, and SOCS7 (Fairchild et al, ). Another excellent example of this conserved function is Pax2, which in the eye is primarily known for its function in optic stork formation, and whose expression has been noted in mature MG of chick but not guinea pigs or dogs (Boije, Ring, López‐Gallardo, Prada, & Hallböök, ; Stanke, Moose, El‐Hodiri, & Fischer, ).…”
Section: Discussionmentioning
confidence: 99%